2016
DOI: 10.1142/s2339547816500096
|View full text |Cite
|
Sign up to set email alerts
|

Responsive filtration membranes by polymer self-assembly

Abstract: Membrane technologies are essential for water treatment, bioprocessing and chemical manufacturing. Stimuli-responsive membranes respond to changes in feed conditions (e.g., temperature, pH) or external stimuli (e.g., magnetic field, light) with a change in performance parameters (permeability, selectivity). This enables new functionalities such as tunable performance, self-cleaning and smart-valve behavior. Polymer self-assembly is a crucial tool for manufacturing such membranes using scalable methods, enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 113 publications
(148 reference statements)
0
15
0
Order By: Relevance
“…However, hydrophobicity is also important in some specific membrane water treatment applications such as oil–water separation and membrane distillation. While previous studies have found good candidates for this class of materials, through targeted design of functional, self‐organizing polymers specifically for this application, better performance can be achieved. The most common approaches here are to either make use of constituents that will segregate to the membrane surface or to employ post‐processing treatments …”
Section: Introductionmentioning
confidence: 99%
“…However, hydrophobicity is also important in some specific membrane water treatment applications such as oil–water separation and membrane distillation. While previous studies have found good candidates for this class of materials, through targeted design of functional, self‐organizing polymers specifically for this application, better performance can be achieved. The most common approaches here are to either make use of constituents that will segregate to the membrane surface or to employ post‐processing treatments …”
Section: Introductionmentioning
confidence: 99%
“…Most studied methods of preventing fouling aim to create highly hydrophilic membrane surfaces through surface functionalization, either by post-treatment [13][14][15][16][17][18][19][20][21][22][23] or by surface-segregating additives. [24][25][26][27][28][29][30][31][32] Zwitterionic materials are strongly fouling resistant as a result of compactly bound water molecules that are organized as a hydration layer around the zwitterionic head groups. [33] To develop fouling resistant and high flux UF membranes, several groups have incorporated zwitterionic groups on membrane surfaces and shown increased resistance to fouling, specifically by protein solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly is a promising tool for generating membranes with functional nanostructures using scalable, easier to implement methods. For example, the self-assembly of a polymer within the pores of a TE membrane through ionic interactions has been reported to narrow the pores down to 6–9 nm, ideal for protein separations but still too large for separating small molecules. The porosity of these membranes is, however, still very low, and tailoring the pore size and the functionality is very difficult and limited by the polymer structure.…”
mentioning
confidence: 99%